Corporate Social Responsibility as a New Form of Social Dialogue - Filek, Janina (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Built on a philosophical and social analysis, the paper’s thesis is that corporate social responsibility is a new form of social dialogue. To support the thesis, the features of social communication (on the level of colloquial language), features of philosophical dialogue, and features of corporate social responsibility dialogue are compared. Following the presentation of the corporate social responsibility dialogue, the anthropological, economic and social advantages of a dialogue between companies and their stakeholders is described. One conclusion the analysis led to is that, in the current social-economic situation, further economic development has been increasingly dependent on a company’s dialogue with its stakeholders. Further benefits a company can derive from conducting a responsible dialogue with stakeholders are also indicated.